Young,fearless,awesome,25 people who changed the world. - Caldwell,Stella (London: Welbeck children's book, 2020)
With inspiring stories of passion and courage, this biography book for kids will motivate a generation of movers and shakers to stand up for what they believe, speak out against injustice, and overcome adversity to create lasting change.
Keywords: English-general knowledge